2021
DOI: 10.36253/qoe-9590
|View full text |Cite
|
Sign up to set email alerts
|

Decades of Party Distrust. Persistence through Reform in Italy

Abstract: One common feature of the Italian political space over the past half century has been the presence of distrust in political parties and the presence of anti-system parties on both the left and the right. Discontent with existing elites and the political system has taken many forms, including referendums altering the electoral system. Both the character of the main parties and the rules by which they are elected have been reformed 4 times since the 1980s. However, as the elections of 2013 and 2018 and the refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In Italy, as in other countries, there is a constant decline in trust in institutions (OECD, 2017 ). A survey conducted in 2019 (before the pandemic) showed that trust in institutions has dwarfed public and political organizations, except the Pope (Demos, 2019 ); moreover, a specific study on political institutions shows that Italians have little faith in parties, parliament, and the government (Bergman et al, 2021 ). After all, since the 1990s the country has been the scene of great political scandals (Pardo, 2004 ) and numerous cases of corruption which, by violating the democratic contract, have partly compromised citizens' trust in the political system (Memoli, 2011 ; Pardo, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, as in other countries, there is a constant decline in trust in institutions (OECD, 2017 ). A survey conducted in 2019 (before the pandemic) showed that trust in institutions has dwarfed public and political organizations, except the Pope (Demos, 2019 ); moreover, a specific study on political institutions shows that Italians have little faith in parties, parliament, and the government (Bergman et al, 2021 ). After all, since the 1990s the country has been the scene of great political scandals (Pardo, 2004 ) and numerous cases of corruption which, by violating the democratic contract, have partly compromised citizens' trust in the political system (Memoli, 2011 ; Pardo, 2018 ).…”
Section: Introductionmentioning
confidence: 99%